Instability of Non-Linear Functional Differential Equations of Fifth Order - Cemil Tunc (Journal of Mathematical and Fundamental Sciences, 2012)
In this paper, we study the instability properties of solutions of a kind of functional differential equations of the fifth order with constant delay. Using the Lyapunov-Krasovskii functional approach, we obtain certain sufficient conditions to guarantee that the zero solution of the equation is unstable.